A comparison study between public and private healthcare sector medicine prices in South Africa. Issue 2 (30th January 2021) - Thaver, Tarryn; Padayachee, Neelaveni; Bangalee, Varsha
Abstract: Objectives: The objectives of the study were to compare price trends, determine price differentials, and equate the average price index of a basket of medicines between the public and private healthcare sectors in South Africa. Methods: A price list consisting of 32 essential medicines available in both the public and private healthcare systems of South Africa was chosen for this study. The price of medicines for the private sector were obtained from the Medicine Price Registry-Open Up website for the period 2014–2018. Public sector medicine prices were obtained from the Department of Health website for the corresponding period. Observations and price trends were identified and analyzed using Microsoft Excel version 2016. Key findings: A total of 74 medicine brands were analyzed in the study. It was found that the prices across both sectors had increased over time, however, the majority of brands (87%) displayed higher prices in the private sector in comparison to the public sector. On average, the price differential between the private and public sector medicines were 395.47%. Conclusions: The study found varying price differences between medicines in the public and private sectors because of the different methodologies used in each. The reasons for changes in medicine prices across the years in both sectors, could not always be clearly determined as both sectors lacked complete transparency in the processes applied to establish medicine prices. Therefore, more transparent medicine price systems need to be considered for the future of South Africa's healthcare system as the country transitions toward universal health coverage.